A wear-resistant polyaryletherketone brush wire material and preparation method thereof
By combining polyaryl etherketone resin and modified carbon nanotubes with polyamide resin, wear-resistant polyaryl etherketone brush wire material is prepared, which solves the problems of easy wear and static electricity in traditional nylon brush wire materials, and achieves higher wear resistance and anti-static properties.
Patent Information
- Application Number
- CN202411991730.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Traditional nylon brushed wire materials are prone to wear when used for a long time or when in contact with hard surfaces, and may produce static electricity, bacteria and dust, affecting service life and range.
A wear-resistant polyaryletherketone brush material is prepared by combining polyaryletherketone resin, modified carbon nanotubes and other additives with polyamide resin. The material maintains mechanical properties under high temperature environments and has excellent heat resistance, chemical corrosion resistance, antibacterial and antistatic properties.
It significantly improves the wear resistance, antibacterial and antistatic properties of the brushed wire material, extends its service life, and expands its application range.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular, relates to a wear-resistant polyaryletherketone brush filament material and a preparation method thereof. Background Art
[0002] Polyamide (PA), commonly known as nylon, refers to a polymer with amide repeating structural units on the polymer chain. It is a general-purpose engineering plastic with a long history and the largest output, and is an important fiber material commonly found in daily life. Nylon brush filament material is a common brush material and is widely used in cleaning, coating, polishing and other industrial fields.
[0003] However, with the continuous development of technology, traditional nylon brush wire materials face some challenges and limitations. When traditional nylon brush wire materials are used for a long time or in contact with hard surfaces, they are easily affected by friction and pressure, resulting in particle wear and peeling. In addition, nylon brush wires will generate static electricity, bacteria, and dust during use, which will have a negative impact on the surrounding electronic devices and working environment, thereby limiting their service life and scope of use. Polyaryletherketone has excellent wear resistance, electrical properties, and chemical corrosion resistance. Therefore, adding polyaryletherketone to nylon brush wire materials can significantly improve the wear resistance and electrical properties of the brush wire materials. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a wear-resistant polyaryletherketone brush wire material and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A wear-resistant polyaryletherketone brush filament material comprises the following raw materials in parts by weight: 50-60 parts of polyamide resin, 20-30 parts of polyaryletherketone resin, 10-20 parts of carbon fiber, 5-15 parts of silicone rubber, 6-12 parts of filler, 4-10 parts of modified carbon nanotubes, 0.5-1.5 parts of coupling agent, 0.3-0.6 parts of ultraviolet absorber, 0.3-0.6 parts of light stabilizer and 0.3-1 parts of lubricant.
[0007] Polyaryletherketone has a high glass transition temperature and melting point, is suitable for use in high temperature environments, and can maintain mechanical properties in a wide range. It also has excellent hot water resistance, fatigue resistance, chemical corrosion resistance, flame retardancy, and wear resistance. In addition, polyaryletherketone also has excellent radiation resistance and electrical properties. Therefore, adding polyaryletherketone to nylon brush wire material can significantly improve the performance of the brush wire material, mainly in terms of high temperature resistance, chemical corrosion resistance, high strength, and wear resistance.
[0008] Furthermore, the filler is one or more of calcium carbonate, fumed silica, and perlite powder.
[0009] Furthermore, the modified carbon nanotubes are prepared by the following steps:
[0010] S1. Blow nitrogen into a dry three-necked flask for 30 minutes to expel air and moisture from the flask, then add hydroxyethyl methacrylate, DBU (1,8-diazobisspiro[5.4.0]undec-7-ene) and chloroform, stir and heat to 60°C, then slowly add trimethyl-1,3-propylenediamine, and keep warm for 48 hours after the addition is complete. After the reaction is completed, cool to room temperature first, and then distill under reduced pressure to obtain intermediate 1; the dosage ratio of hydroxyethyl methacrylate, trimethyl-1,3-propylenediamine, DBU and chloroform is 12.1mL:15.8mL:3mL:120mL;
[0011] The molar ratio of hydroxyethyl methacrylate to trimethyl-1,3-propylenediamine is controlled to be 1:1.05-1.1, then hydroxyethyl methacrylate and trimethyl-1,3-propylenediamine undergo Michael addition reaction under heating and the catalysis of DBU. The reaction process is as follows:
[0012]
[0013] S2. Add intermediate 1, triethylamine and chloroform to a dry three-necked flask under nitrogen protection, stir and dissolve, heat to 60°C, then slowly add tetradecane bromide, keep at 60°C for 4h after the addition, cool to room temperature after the reaction, and distill under reduced pressure to obtain intermediate 2; the amount ratio of intermediate 1, tetradecane bromide, triethylamine and chloroform is 12.3g:32.1mL:15.3mL:180mL;
[0014] Triethylamine is used as an acid binding agent, and the molar ratio of intermediate 1 to tetradecane bromide is controlled to be 1:2.1-2.2, so that the tertiary amine of intermediate 1 and -Br of tetradecane bromide undergo nucleophilic substitution reaction, and the reaction process is as follows:
[0015]
[0016] S3. Add carbon nanotubes and 65% nitric acid into a three-necked flask, heat to 80°C, reflux and stir for 6 hours, cool to room temperature after the reaction, filter and wash with deionized water until the filtrate is neutral, dry the filter residue at 110°C for 12 hours to obtain acidified carbon nanotubes; add intermediate 2, acidified carbon nanotubes and dimethyl sulfoxide into a dry three-necked flask, stir evenly and slowly add concentrated sulfuric acid, heat to 100°C and stir to react for 5 hours after the addition is complete, cool to room temperature after the reaction is completed, filter and wash with deionized water until the filtrate is neutral, dry the filter residue at 110°C for 12 hours to obtain modified carbon nanotubes; the amount ratio of carbon nanotubes to nitric acid is 10g:300mL; the amount ratio of acidified carbon nanotubes, intermediate 2, concentrated sulfuric acid and dimethyl sulfoxide is 8g:1.6g:0.04g:140mL.
[0017] Under the catalytic action of heating and concentrated sulfuric acid, the hydroxyl groups of intermediate 2 and the carboxyl groups on the surface of the acidified carbon nanotubes undergo esterification reaction. The reaction process is as follows:
[0018]
[0019] A quaternary ammonium salt structure is grafted onto the surface of the acidified carbon nanotube to prepare a modified carbon nanotube. The surface of the modified carbon nanotube contains a lipophilic ester group and a long carbon chain. According to the principle of similar compatibility, the modified carbon nanotube of the present invention has good compatibility with other raw materials. The modified carbon nanotube can be fully dispersed in the brush wire material, and then the carbon nanotube and the quaternary ammonium salt structure in the modified carbon nanotube can fully play their role.
[0020] Carbon nanotubes can significantly improve the strength, hardness and toughness of brush filament materials, enabling them to maintain high wear resistance and impact resistance under high pressure, high temperature and harsh environments.
[0021] Quaternary ammonium salt structure is antibacterial by destroying cell membrane structure, making protein denaturation, interfering enzyme system, changing cell membrane permeability, interfering nucleic acid and protein synthesis these five aspects.The strength of quaternary ammonium salt structure antimicrobial activity is mainly determined by the chain length of alkyl chain on its N atom, and the length of alkyl chain is greater than 10 carbon atoms or less than the best quaternary ammonium salt structure antimicrobial activity of 16 carbon atoms, and when carbon number is 14, antibacterial property is best.And in the quaternary ammonium salt structure of modified carbon nanotube of the present invention, the length of alkyl chain is 14 carbon atoms, therefore, modified carbon nanotube has excellent antimicrobial property.In addition, quaternary ammonium salt, as a kind of cationic surfactant, can effectively absorb airborne moisture because of its special chemical structure and property, thereby shows excellent antistatic effect.
[0022] Therefore, the modified carbon nanotubes of the present invention can effectively improve the antibacterial, antistatic, wear resistance and impact resistance of the brush filament material.
[0023] Furthermore, the coupling agent is one or more of isopropyl tri(dioctyl pyrophosphate) titanate, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, and 3-(methacryloyloxy)propyltrimethoxysilane.
[0024] Furthermore, the ultraviolet absorber is one or more of ultraviolet absorber UV-P, ultraviolet absorber UV-9, ultraviolet absorber UV-531, and ultraviolet absorber UVP-327.
[0025] Furthermore, the light stabilizer is one or more of the light stabilizer AM-101, the light stabilizer GW-540, the light stabilizer 744, and the light stabilizer HPT.
[0026] Furthermore, the lubricant is one or more of stearic acid amide, ethylene bis stearamide, zinc stearate, calcium stearate, and magnesium stearate.
[0027] A method for preparing a wear-resistant polyaryletherketone brush filament material comprises the following steps:
[0028] Weigh each raw material by weight, first add all the raw materials into a mixer and mix them evenly, then perform a melt treatment, followed by vacuum stirring, cooling, washing, and drying, then extrude and shape them through a twin-screw extruder, and finally use a wire drawing machine to draw and shape them to obtain a wear-resistant polyaryletherketone brush wire material.
[0029] Beneficial effects of the present invention: The brush wire material of the present invention is added with a polyaryletherketone resin having excellent properties such as heat resistance, wear resistance, and chemical corrosion resistance, and is also added with modified carbon nanotubes containing carbon nanotubes and quaternary ammonium salt structures. In addition, the modified carbon nanotubes have good dispersibility and can fully play their role. Therefore, under the joint action of various raw materials, the brush wire material of the present invention has excellent and stable wear resistance, antibacterial and antistatic properties, and has excellent comprehensive performance. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1, preparing modified carbon nanotubes, the specific steps are as follows:
[0032] S1. Blow nitrogen gas into a 250 mL dry three-necked flask for 30 min to expel air and moisture in the flask, then add 12.1 mL of hydroxyethyl methacrylate, 3 mL of DBU and 120 mL of chloroform, stir and heat to 60°C, then slowly add 15.8 mL of trimethyl-1,3-propylenediamine, keep warm for 48 h after the addition is complete, cool to room temperature after the reaction is completed, and then distill under reduced pressure to obtain intermediate 1;
[0033] S2. Under nitrogen protection, add 12.3 g of intermediate 1, 15.3 mL of triethylamine and 180 mL of chloroform to a 500 mL dry three-necked flask, stir to dissolve and then heat to 60°C, then slowly add 32.1 mL of tetradecane bromide, keep warm at 60°C for 4 h after the addition is complete, cool to room temperature after the reaction is completed, and distill under reduced pressure to obtain intermediate 2;
[0034] S3. Add 10g carbon nanotubes and 300mL nitric acid with a mass fraction of 65% into a 500mL three-necked flask, heat to 80℃, reflux and stir for 6h, cool to room temperature after the reaction, filter and wash with deionized water until the filtrate is neutral, dry the filter residue at 110℃ for 12h to obtain acidified carbon nanotubes; add 1.6g intermediate 2, 8g acidified carbon nanotubes and 140mL dimethyl sulfoxide into a 500mL dry three-necked flask, stir evenly and slowly add 0.04g concentrated sulfuric acid, heat to 100℃ and stir to react for 5h after the addition is complete, cool to room temperature after the reaction is completed, filter and wash with deionized water until the filtrate is neutral, dry the filter residue at 110℃ for 12h to obtain modified carbon nanotubes.
[0035] Example 2, preparing wear-resistant polyaryletherketone brush wire material, the specific steps are as follows:
[0036] Weigh 50 parts of polyamide resin, 20 parts of polyaryletherketone resin, 10 parts of carbon fiber, 5 parts of silicone rubber, 6 parts of calcium carbonate, 4 parts of modified carbon nanotubes prepared in Example 1, 0.5 parts of 3-(methacryloyloxy)propyltrimethoxysilane, 0.3 parts of ultraviolet absorber UV-P, 0.3 parts of light stabilizer AM-101, and 0.3 parts of stearic acid amide by weight. First, add all the raw materials into a mixer and mix them evenly, then melt treat them, followed by vacuum stirring, cooling, washing, and drying, and then extrude them into shape through a twin-screw extruder, and finally use a wire drawing machine to draw and shape them to obtain a wear-resistant polyaryletherketone brush wire material.
[0037] Example 3, preparing wear-resistant polyaryletherketone brush wire material, the specific steps are as follows:
[0038] Weigh 55 parts of polyamide resin, 27 parts of polyaryletherketone resin, 18 parts of carbon fiber, 12 parts of silicone rubber, 5 parts of calcium carbonate, 5 parts of fumed silica, 8 parts of modified carbon nanotubes prepared in Example 1, 0.6 parts of isopropyl tri(dioctylpyrophosphate acyloxy) titanate, 0.3 parts of 3-aminopropyltrimethoxysilane, 0.3 parts of vinyltrimethoxysilane, 0.2 parts of ultraviolet absorber UV-9, 0.2 parts of ultraviolet absorber UV-531, 0.2 parts of light stabilizer GW-540, 0.2 parts of light stabilizer 744, 0.4 parts of ethylenebisstearamide, and 0.4 parts of zinc stearate by weight. First, add all the raw materials into a mixer and mix them evenly, then melt treat them, followed by vacuum stirring, cooling, washing, and drying, then extrude and shape them through a twin-screw extruder, and finally use a wire drawing machine to draw and shape them to obtain a wear-resistant polyaryletherketone brush wire material.
[0039] Example 4, preparing wear-resistant polyaryletherketone brush wire material, the specific steps are as follows:
[0040] Weigh 60 parts of polyamide resin, 30 parts of polyaryletherketone resin, 20 parts of carbon fiber, 15 parts of silicone rubber, 4 parts of calcium carbonate, 4 parts of fumed silica, 4 parts of perlite powder, 10 parts of modified carbon nanotubes prepared in Example 1, 0.5 parts of isopropyl tri(dioctylpyrophosphate acyloxy) titanate, 0.5 parts of 3-aminopropyltriethoxysilane, 0.5 parts of vinyltriethoxysilane, 0.3 parts of ultraviolet absorber UV-531, 0.3 parts of ultraviolet absorber UVP-327, 0.3 parts of light stabilizer 744, 0.3 parts of light stabilizer HPT, 0.5 parts of calcium stearate, and 0.5 parts of magnesium stearate by weight. First, add all the raw materials into a mixer and mix them evenly, then melt-treat them, followed by vacuum stirring, cooling, washing, and drying, and then extrude and shape them through a twin-screw extruder, and finally use a wire drawing machine to draw and shape them to obtain a wear-resistant polyaryletherketone brush wire material.
[0041] Comparative Example 1: Preparation of polyaryletherketone brush filament material, the specific steps are as follows:
[0042] The remaining steps remain unchanged, only the modified carbon nanotubes in Example 2 are removed to prepare the polyaryletherketone brush filament material.
[0043] Comparative Example 2: Preparation of polyaryletherketone brush filament material, the specific steps are as follows:
[0044] The remaining steps remained unchanged, except that the modified carbon nanotubes in Example 2 were replaced by 3.2 parts of carbon nanotubes without any treatment and 0.8 parts of didodecyl dimethyl ammonium chloride to prepare the polyaryletherketone brush filament material.
[0045] Performance Testing
[0046] The polyaryletherketone brush filament materials prepared in Examples 2-4 and Comparative Examples 1-2 were subjected to the following performance tests:
[0047] (1) Notched impact strength test: According to GB / T1843 standard and GB / T2918 requirements, the notched impact strength is tested using a cantilever beam impact testing machine;
[0048] (2) Tensile performance test: A universal material testing machine is used to test the tensile strength per unit area. The tensile strength test method is based on GB1040-92 Plastic Tensile Performance Test Method;
[0049] (3) Surface resistivity test: Test surface resistivity according to IEC60093 requirements;
[0050] (4) Wear resistance test: Use a simulated friction tester with a load of 500g and a test time of 1000 times, using a bidirectional scraping method; record the sample weight at the end of the test, and calculate the wear loss and friction coefficient.
[0051] The test results of all items are shown in the following table:
[0052]
[0053] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0054] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A wear-resistant polyaryletherketone brush wire material, characterized in that: The invention comprises the following raw materials in parts by weight: 50-60 parts of polyamide resin, 20-30 parts of polyaryletherketone resin, 10-20 parts of carbon fiber, 5-15 parts of silicone rubber, 6-12 parts of filler, 4-10 parts of modified carbon nanotubes, 0.5-1.5 parts of coupling agent, 0.3-0.6 parts of ultraviolet absorber, 0.3-0.6 parts of light stabilizer and 0.3-1 parts of lubricant; Wherein, the modified carbon nanotubes are prepared by the following steps: S1. After nitrogen is blown into the flask, hydroxyethyl methacrylate, 1,8-diazobispiro[5.4.0]undec-7-ene and chloroform are added, the temperature is raised to 60°C with stirring, trimethyl-1,3-propylenediamine is added, the reaction is carried out for 48 hours, the reaction is cooled, and the intermediate 1 is obtained by distillation under reduced pressure; the dosage ratio of hydroxyethyl methacrylate, trimethyl-1,3-propylenediamine, DBU and chloroform is 12.1mL:15.8mL:3mL:120mL; S2. Add intermediate 1, triethylamine and chloroform to a flask under nitrogen protection, stir and heat to 60°C, add tetradecane bromide, react for 4 hours, cool, and distill under reduced pressure to obtain intermediate 2; the amount ratio of intermediate 1, tetradecane bromide, triethylamine and chloroform is 12.3 g:32.1 mL:15.3 mL:180 mL; S3, adding carbon nanotubes and nitric acid to a flask, heating to 80°C and stirring for 6h, cooling, filtering, washing, and drying to obtain acidified carbon nanotubes; adding intermediate 2, acidified carbon nanotubes and dimethyl sulfoxide to a flask, stirring and adding concentrated sulfuric acid, heating to 100°C and reacting for 5h, cooling, filtering, washing, and drying to obtain modified carbon nanotubes; the amount ratio of carbon nanotubes to nitric acid is 10g:300mL; the amount ratio of acidified carbon nanotubes, intermediate 2, concentrated sulfuric acid and dimethyl sulfoxide is 8g:1.6g:0.04g:140mL; The coupling agent is one or more of isopropyl tri(dioctyl pyrophosphate) titanate, 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, vinyl trimethoxysilane, vinyl triethoxysilane, and 3-(methacryloyloxy)propyl trimethoxysilane.
2. A wear-resistant polyaryletherketone brush wire material according to claim 1, characterized in that: The filler is one or more of calcium carbonate, fumed silica, and pearlite powder.
3. The wear-resistant polyaryletherketone brush wire material according to claim 1, characterized in that: The ultraviolet absorber is one or more of the ultraviolet absorber UV-P, ultraviolet absorber UV-9, ultraviolet absorber UV-531, and ultraviolet absorber UVP-327.
4. The wear-resistant polyaryletherketone brush wire material according to claim 1, characterized in that: The light stabilizer is one or more of the light stabilizer AM-101, the light stabilizer GW-540, the light stabilizer 744, and the light stabilizer HPT.
5. The wear-resistant polyaryletherketone brush wire material according to claim 1, characterized in that: The lubricant is one or more of stearic acid amide, ethylene bis stearamide, zinc stearate, calcium stearate, and magnesium stearate.
6. The method for preparing a wear-resistant polyaryletherketone brush filament material according to claim 1, characterized in that: The following steps are involved: Weigh each raw material by weight, first add all the raw materials into a mixer and mix them evenly, then perform a melt treatment, followed by vacuum stirring, cooling, washing, and drying, then extrude and shape them through a twin-screw extruder, and finally use a wire drawing machine to draw and shape them to obtain a wear-resistant polyaryletherketone brush wire material.
Citation Information
Patent Citations
Abrasive containing brush wire for rolled steel finishing production line and preparation method for abrasive containing brush wire
CN110511564A
Wear-resistant composite material, wire drawing process thereof and application of wear-resistant composite material in brush
CN116622232A
Anti-static wear-resistant plastic master batch and preparation process thereof
CN118440421A